Ecological Religious-Cultural: New Direction of Ecological Paradigm in the Integration Frame of Maqashid Sharia and Tapanuli Indigenous Religious Concepts - Ibrahim Siregar; Suheri Sahputra Rangkuti (DINIKA : Academic Journal of Islamic Studies, 2024)
The ecological paradigm in this context refers to an approach that combines environmental principles with religious values and local wisdom in an effort to maintain ecological sustainability and build harmonious relationships between humans and nature. This study used an integrative approach with convergence analysis. In the mechanism of this approach, Maqāṣid al-Sharīʿah and Tapanuli indigenous religious concepts are used in a complementary manner in building a paradigm to achieve ethical goals related to ecology. The result of the integration of Maqāṣid al-Sharīʿah and the traditional religious concept of Tapanuli found that Mangholongi Bona Bulu as a new religious ethic in responding to ecology. The shift from a pseudo-paradigm to an objective is a necessity in building a sustainability ecology. This study makes an important contribution to the development of ecological-religious cultural theory and practice, as well as providing a deeper understanding of religious values and local wisdom in the context of the environment. The implications of this research are the importance of incorporating ecological perspectives in the development of sustainable policies and practices, as well as the need to explore and respect religious traditions and local wisdom in maintaining ecological balance and strengthening human relationships with nature.